Efektivitas Pusat Kesejahteraan Sosial “As Salam” Desa Katapang Kecamatan Katapang Kabupaten Bandung - Dwi Heru Sukoco (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2021)
Center for Social Welfare (Puskesos) "As Salaam" is a village-level integrated service and referral institution for poor families by providing easy access to Social Protection and Poverty Reduction Programs (SPPRP). A qualitative approach was used in this research with helps from manager, facilitator, village head, chairman, and beneficiaries as informants. Data was collected by triangulate, combining interview, observation, and documentation study. Data validation was performed by credibility, transferability, dependability, and confirmability techniques. Data was analyzed by The Mile Model & Huberman. The results showed that Puskesos "As Salaam" is new but has been able to achieve its goals. It has ability to: (1) become data center; (2) serve, handle, and resolve the grievances of poor families; (3) refer complaints to higher services; and (4) facilitate the improvement of Social Welfare Integrated Data (SWID). Some achievements: awarded as the best puskesos in Bandung Regency, visited by domestic and foreign guests, done comparative study places, research locations and student field practices. So, it is a growing puskesos whose performance’s "quite effective". Recommendations: (1) It should be a one-stop village-level integrated service institution; (2) Conduct data collection immediately so that poor families are registered in SWID, (3) Socialize not only Kemensos’ program, but also other ministries/communities’; (4) Provide direct services; (5) Provide not only SPPRP, but also social rehabilitation and empowerment; (6) Provide SKPD representatives in Puskesos; and (7) Managers should be high-ranking primary officials to be able to coordinate with District SKPD head.